2013
DOI: 10.1038/cdd.2013.86
|View full text |Cite
|
Sign up to set email alerts
|

MEK drives cyclin D1 hyperelevation during geroconversion

Abstract: When the cell cycle becomes arrested, MTOR (mechanistic Target of Rapamycin) converts reversible arrest into senescence (geroconversion). Hyperexpression of cyclin D1 is a universal marker of senescence along with hypertrophy, beta-Gal staining and loss of replicative/regenerative potential (RP), namely, the ability to restart proliferation when the cell cycle is released. Inhibition of MTOR decelerates geroconversion, although only partially decreases cyclin D1. Here we show that in p21-and p16-induced senesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 75 publications
3
78
0
Order By: Relevance
“…1B), as observed by others. 41,42,51,52 Also interestingly, PD0332991 treatment prevented the disappearance of p21 but not of p27 (Fig. 1B).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…1B), as observed by others. 41,42,51,52 Also interestingly, PD0332991 treatment prevented the disappearance of p21 but not of p27 (Fig. 1B).…”
Section: Resultsmentioning
confidence: 75%
“…Nevertheless, other mechanisms might concur to cyclin D1 accumulation in PD0332991-arrested cells. As an early marker of conversion to senescence (geroconversion), MEK-dependent hyperinduction of cyclin D1 in response to PD0332991 52 was also observed in the absence of a large increase of p21. 42 Arrest of PD0332991 treatment induces DNA synthesis and pRb phosphorylations in serumdeprived cells…”
Section: Resultsmentioning
confidence: 95%
“…It has also been shown that senescent human fibroblasts express high levels of cyclin D1, [23][24][25][26] and cell cycle deregulation often induces cellular senescence. 27 Thus, cyclin D1 overexpression is considered a marker of cellular senescence. Importantly, senescent cells are negative for PCNA, because cell growth has been arrested.…”
Section: Irreversible Nuclear Cyclin D1 Accumulation Following Longtementioning
confidence: 99%
“…Conversely, cells undergo senescence, when their cell cycle is arrested in the presence of growth stimulation (1)(2)(3)(4)(5). Recently, it was demonstrated that the difference between reversible quiescence and irreversible senescence is determined by an active mammalian target of rapamycin (mTOR) pathway in senescent cells (6)(7)(8)(9)(10)(11). When cell cycle is arrested and mTOR is stimulated by serum growth factors or oncoproteins such as Ras, the arrested cells undergo senescence (1,4,12,13).…”
mentioning
confidence: 99%
“…The conversion from reversible cell cycle arrest to senescence is named gerogenic conversion (or geroconversion) (12). Conditions that inhibit mTOR (6,14,15) also inhibit geroconversion while causing or maintaining cell cycle arrest (6,7,10).…”
mentioning
confidence: 99%